Understanding customer experience over time and customer citizenship behavior in retail environment: The mediating role of customer brand relationship strength - Hoa PhamThi; Trong Nghia Ho (Cogent Business & Management, 2024)
In the retail industry, customer experience over time is the overall customer perception after making transactions with retailers. This concept has been increasingly important since it can help retailers to gain competitive advantages. However, there has been a lack of studies investigating how customer experience over time inspires customers to engage in customer citizenship behavior, especially via the mediation of customer-brand relationship strength. To bridge the gap, this study examines the mediating role of customer-brand relationship strength on the associations between retail customer experience over time and customer citizenship behavior in retail industry. Specifically, the four components of customer-brand relationship strength including brand commitment, self-brand connection, brand intimacy, and customer satisfaction are investigated their mediations on the relationships between retail customer experience over time and customer citizenship behavior. Besides, the four dimensions of retail customer experience over time (i.e. product experience, peace of mind, moments-of-truth, and outcome focus) and of customer citizenship behavior (i.e. advocacy, feedback, helping, and tolerance) are also investigated. A self-administrated survey was conducted utilizing a convenient sampling method. The data, collected from 341 customers of electronics and home appliance retailers, was analyzed by employing PLS-SEM. The results indicate that customer experience over time induces customer brand relationship strength, which subsequently affects customer citizenship behavior. The data analysis results also figure out the mediating role of customer brand relationship strength on the relationship between customer experience over time and customer citizenship behavior. These findings contribute significantly to theoretical and practical implications in retail environment.
Keywords: 650; customer brand relationship strength; customer citizenship behavior; customer experience over time; moments-of-truth; retail environment; touchpoint